Spanking and externalizing problems: Examining within‐subject associations - Pritsker, Joshua (Child development, 2021)
This study examined the effects of spanking on externalizing on a within‐subject level, while excluding causally irrelevant between‐subject variance. Results from two longitudinal studies which used participants from the Child Development Project (n = 585) were reanalyzed with a random‐intercept cross‐lagged panel model using yearly measurements over ages 6–8. After removing between‐subject variance, there were no significant effects of general spanking on externalizing (β = .06, .07). However, when done without objects and at a rate of about once per month or less, spanking showed beneficial effects (β = −.17, −.21). Results suggest that previous findings may be due to a failure to separate between‐subject and within‐subject variance. Additionally, results illustrate the need to examine limited spanking separately from more general forms of physical punishment.